CASE MANAGEMENT FOR PEOPLE WITH STROKE: QUASI-EXPERIMENTAL STUDY - de Souza, Pollyanna Bahls; Mantovani, Maria de Fátima; Peres, Aida Maris; Marcon, Sonia Silva; Madureira, Alexandra Bittencourt; Gevert, Vania Gryczak (Cogitare Enfermagem, 2022)
Objective: to compare the effect of intervention by nurse-case manager on risk factors and blood pressure in post-stroke people. Method: quasi-experimental study conducted over six months with 14 post-stroke patients in southern Brazil. The intervention with case management consisted of nursing consultations, individualized educational actions and referrals to other professionals, operationalized in three home visits and six telephone contacts. For data analysis, descriptive statistics and Fisher’s test were used, with a significance level of p≤0.05. Results: Reduction of smoking (p=0.0414), alcohol intake (p=0), sodium consumption (p=0.0024), fat (p=0.0027), carbohydrate (p=0.0203) and sugar (p=0.0111), increased physical activity (p=0.0382) and non-significant reduction of blood pressure levels were observed. Conclusion: Nurse-led case management is a valid strategy to follow people recovering from stroke.